2018
DOI: 10.1038/s41433-018-0166-4
|View full text |Cite
|
Sign up to set email alerts
|

The management of macular hole retinal detachment and macular retinoschisis in pathological myopia; a UK collaborative study

Abstract: PPV is the only surgical procedure performed for the management of MHRD and MRS amongst the study participants. Success rates and visual outcomes are limited for MHRD and consistent with the current literature for MRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
0
6
0
1
Order By: Relevance
“…PM with macular hole RD is common in the Chinese population [ 30 ]. Like previously reported, they had some unique characteristics: delayed presentation, slow progression, and worse functional and anatomic prognosis [ 31 ], requiring second or combined surgery [ 28 , 30 ]. Surgery on the PM patient with macular hole RD was suspended during the COVID-19 pandemic because most ophthalmologists and patients preferred follow-up until the visual symptoms were aggregated.…”
Section: Discussionmentioning
confidence: 90%
“…PM with macular hole RD is common in the Chinese population [ 30 ]. Like previously reported, they had some unique characteristics: delayed presentation, slow progression, and worse functional and anatomic prognosis [ 31 ], requiring second or combined surgery [ 28 , 30 ]. Surgery on the PM patient with macular hole RD was suspended during the COVID-19 pandemic because most ophthalmologists and patients preferred follow-up until the visual symptoms were aggregated.…”
Section: Discussionmentioning
confidence: 90%
“…Vitrectomy is the most popular surgical procedure for MTM including retinoschisis and macular hole [ 16 , 17 ]. However, few studies have focused on the surgical management of FD.…”
Section: Discussionmentioning
confidence: 99%
“…In the retina, structural damage almost always precedes functional damage. RNFL thinning found in idiopathic macular holes may lead to retinal detachment, 27,28 a pathological mechanism reported in patients with early‐stage glaucoma 7 . Another study reported reduced thickness of RNFL and GCIPL in idiopathic retinal telangiectasia, a neurodegenerative retinal disease characterized by alterations in the macular capillary network, neurosensory atrophy, and occasional subretinal neovascularization 29 .…”
Section: Discussionmentioning
confidence: 99%